COUNTER-CLAIMING FOR A CRIME NARRATIVE: AN EVALUATION OF THE DEFENDANT’S PLEA AT THE CORRUPTION CRIMINAL COURT - Hermawan, Ripan; Rahyono, F.X.; Dallyono, Ruswan (Universitas Pendidikan Indonesia, 2021)
In a criminal trial, the plea of the accused is arguably a very important appraising discourse tool functioning mainly to counter the crime narrative made by public prosecutors in their indictment and closing statement. As an appraisal instrument, the plea represents the stance of the accused with regards to the facts of the case as well as the legal aspects of the alleged crime. In this regard, the plea may serve both argumentative and persuasive functions and may shape, to some extent, the understanding and the consideration of the judges who decide on the case. The study, which is qualitative in nature, uses Martin and White’s appraisal theory (Martin and White, 2005) to investigate evaluation strategies employed by an accused of a corruption case in his plea. Evaluation strategies are defined here as strategies in discourse used to counter the crime narrative by employing relevant evaluative resources. The result of the analysis shows that the accused strategically uses the three main discourse semantics resources, i.e. engagement, attitude, and graduation. The contractive options of engagement (deny, counter, and pronounce) are used to counter aspects of the crime narrative, while judgment of propriety (social sanction) and capacity (social esteem) of the attitude component are employed mainly to evaluate aspects of the crime narrative negatively and aspects of the counter narrative positively. Furthermore, amplification and quantification options of the graduation component are used to strengthen the degree of evaluation. It can be concluded that the narrative of plea is arguably an important evaluative instrument which, strategically and professionally constructed, may help the accused convince the judges of his/her innocence.